Zwischen Kaffeehaus und Kanzel: Praktische Theologie im Wechselspiel mit den Künsten (Evangelische Verlagsanstalt, 2023)
Martin Nicol's enthusiasm for the arts motivated pastors in Erlangen, Braunschweig and elsewhere not to defer their private passion for this or that art to the home, but to take it with them into their everyday professional lives. This volume brings together essays by Martin Nicol in which poems, cantatas and films inspire an aesthetically oriented practical theology. With these texts, Nicol wants to whet your appetite for a practice that is on the trail of God's beauty in interplay with the arts, even in a theologically, politically and culturally changed landscape.